Impact of lake surface temperatures simulated by the FLake scheme in the CNRM-CM5 climate model. Issue 1 (1st December 2016) - Le Moigne, Patrick; Colin, Jeanne; Decharme, Bertrand
Abstract : The impact of lakes on climate is investigated in a set of global simulations performed with the CNRM-CM5 climate model coupled to the FLake lake scheme. First, offline simulations driven by ERA-Interim (ERA-I hereafter) reanalysis are performed on a limited set of lakes to find the best FLake parameters setting. Optimal values of lake depth, ice albedo and light extinction coefficient are defined by evaluating the model's performance in different climates for surface temperature and lake ice duration. Second, global simulations are performed with and without FLake to assess the impact of lake representation on the surface energy balance and the boundary layer characteristics. Results indicate that FLake simulates the lake surface temperature satisfactorily in an offline mode and that the use of FLake coupled to CNRM-CM5 improves some of the global biases found in the climate model. It is also shown that lakes impact the surface energy budget significantly at a regional scale; however, the impact on climate is rather limited. Finally, future developments related to the implementation of a more physical snow model and a water balance in FLake are discussed.